Diazonium-modified zeolite fillers. Effect of diazonium substituent position on the filler surface modification and the mechanical properties of phenolic/zeolite composites. (October 2018) - Sandomierski, Mariusz; Strzemiecka, Beata; Grams, Jacek; Chehimi, Mohamed M.; Voelkel, Adam
Abstract: Composite interfaces and interphases are critical regions that dictate the filler-matrix adhesion with an important output in terms of mechanical properties of the composites. Whilst much has been demonstrated with the filler surface modification, the diazonium interface chemistry has rarely been explored in this sense. Herein, zeolite Micro20 was modified with in situ generated diazonium salts from the 2- and 4-aminobenzyl alcohols and characterized by complementary analytical tools. Moreover, the substituent position effect of the CH2 OH group is examined with the synthesis of 2- and 4-hydroxymethylbenzenediazonium compounds. Finally, the zeolites having CH2 -OH groups were mixed with phenolic resins and the composites were obtained by thermal curing. It is found that the ortho position induces steric hindrance and results in lower extent of surface modification compared to the para-position. Before cure, the resin-filler was found to flow in the case of the ortho position, whereas the para position yields a viscous formulated blend. After cure, the composite shows superior mechanical properties in the case of use in the formulation of the para position. This could be due to two effects: the higher concentration of reactive sites in the para position borne by the filler for reaction towards resins, and ease of reaction between the surface bound groups in the para position with the resin. The ortho position yields less surface bound reactive groups and less efficient reaction with the resins due to steric hindrance. This works highlights subtle position effects of reactive groups employed to fabricate specially surface-modified fillers. It stresses the role of isomer position in the design of high performance composites.